FRASA ISOLEK DAYAK BA’NGAPE: KAJIAN SINTAKSIS - Klara, Dina Kristina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Isolek Dayak Ba’Ngape (IDB) is a local language in West Kalimantan, exactly in Ansang Village, Subdistrict of Menyuke, Landak Regency. Ansang Village has been chosen as a research object because their daily language is IDB itself. The problems in this research are elements distribution of phrase, phrase categories, and the meaning of IDB phrase. The method used is descriptive qualitative. The data is IDB phrase that used by Ansang citizen. The data source is IDB which is talked by three native. The technique to took the data by interview and discussing, moreover the tools used are list of vocabularies (swadesh) and folklore by native. Based on data analysis, the result of the research are:(1)there are two distribution elements of phrase such as endocentric phrase (attributive endocentric phrase, endocentric coordinative phrase, appositive endocentric phrase) and exocentric phrase; (2)there are six phrase categories of IDB such as nominal phrase, verbal phrase, numeral phrase, adverbial phrase, preposition phrase and adjective phrase; (3)there are five meaning of IDB phrase based on its phrase categories such as nominal phrase meaning, verbal phrase meaning, adverbial phrase meaning, preposition phrase meaning and adjective phrase meaning. Keywords: Phrase, Phrase Distribution, Phrase Categories, Phrase Meaning, Isolek Dayak Ba’Ngape